Relationships between different field test performance measures in elite goalball players - Goulart-Siqueira, G.; Benitez-Flores, S.; Ferreira, A. R. P.; Zagatto, A. M.; Foster, C.; Boullosa, D. (Sports, 2019)
Goalball is a Paralympic sport involving people with visual impairment. Little is known about the physical fitness of elite players of this sport, as previous studies only evaluated body composition and aerobic capacity. Thus, the aim of this study was to describe the performance of elite goalball players in different physical tests and to look for relationships between them. Eleven elite Brazilian goalball players, seven males and four females, were evaluated for body composition, maximal handgrip isometric force (MHGF), countermovement jump (CMJ), throwing velocity (TV) and the Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1). Players produced 41.54 ± 8.41 kgf in MHGF, 34.81 ± 7.2 cm in CMJ, 14.21 ± 1.89 m·s-1 in TV, and 505 ± 313 m in Yo-Yo IR1, with an estimated maximum oxygen consumption (VO2max) of 40.64 ± 2.63 mL·kg-1·min-1. Most performance tests exhibited moderate to high correlations among them, while the percentage of body fat correlated with both the CMJ and Yo-Yo IR1 results. The current study reveals that CMJ could be a valuable monitoring tool as it was correlated with all other performance tests. The highest correlation observed was with TV (r = 0.754; p < 0.05), which is a key capacity in goalball. Moreover, high levels of body fat could be detrimental to anaerobic performance.